Environmental governance in the anthropocene: the case of the Nalus as an arena of ontological conflict - Indi, Lucas Jaime (Pós - Revista Brasiliense de Pós-Graduação em Ciências Sociais, 2025)
The purpose of this paper is to examine how the creation of an environmental preservation project in Cantanhez, Guinea-Bissau, fits into a structural context of economic and ideological interests that generate conflicts between different ontological perspectives on the utility of nature. To achieve this goal, we question the neoliberal institutions that shape democracy under the influence of Holocene thinking, (Hardt, 2019) which has established the main categories of contemporary environmental governance and the political instruments that determine ways of relating to the environment. The methodological approach adopted in this work is based on a qualitative approach whose techniques consist of a literature review and document analysis. We present perspectives that intertwine an ontological approach that challenges the hegemonic foundations of Western environmental governance. Without losing sight of the fact that it is these foundations that integrate the environment into a neoliberal eco-market where the knowledge that underlies ontological modes of mediating nature-society gains eco-market value. Debating environmental governance in the Anthropocene as a variable that determines and has effects on other ontologies implies problematizing the ontological assumptions of environmental governance by democratic neoliberal institutions.